Psychosocial analysis of the Peruvian sensationalist press discourse and attitudes of its readers - Montero López, Victor (2008)
One explored explanatory theories of subjects like the identity, attributions, motivations, social mechanisms of defense, communication, representations and attitudes; as well as investigations on mass media speeches. Storing became of unit of daily sensationalists for its analysis. Group with young people of diverse sectors like college students of San Marcos, or popular sectors like Window or students like of the school Jose Granda soon went to make focus. Also, observations in diverse districts and points of sale of newspapers were made (kioscos), soon to gather some testimonies. It was approached soon with a survey to representative sectors of young people like university house of San Marcos in the district of the Victory, Agrarian University of the Molina, University Ruiz de Montoya, school Jose Granda in San Martin de Porres and school of Chorrillos, young people in Ventanilla and Pamplona and PPJJ Chapi in Callao, obtaining a universe varied with comparative aims.